Value added products from agrowaste - Anand, Barapatre; Sudha, Sahu; Keshaw, Aadil; Harit, Jha (Recent Research in Science and Technology, 2013)
India generates over 400 million tones of agro-forest residues. Agricultural and forest biomass are available in large enough quantities to be considered for large-scale production of alcohol-based fuels. Chhattisgarh is considered rice bowl of India. Rice is an annual crop and one of the byproduct is rice straw. Rice straw can be used as the source of biomasss and lignin.The various other non-woods available are wheat straw, rice straw, barley straw, grass seed straw, flax coil seed, corn stalks, sorghum stalks, sugarcane bagasse, reeds, hemp fiber, sabai grass, cotton staples, stem fibers (hemp, kenaf, jute) etc .Technologies based on the efficient conversion of low quality or waste lignocellulosic residues into fuel and industrially important chemicals represent possible long-term solution to a number of major global problems. The farmers will be benefited economically as their agricultural by-products will provide better cost sharing. The cost of production of chemicals will also be reduced due to involvement of microorganisms and biochemical processes involved therein. The lignin and cellulose obtained from agrowaste can provide a major carbon resource for biotransformation technologies and are anticipated to provide a novel avenue for non-polluting industries by reducing carbon emission.Lignin, as the most abundant natural aromatic material, is being considered for new economical applications such as bio-fuel, binder, dispersant or emulsifier, phenolic resins, carbon fibers automotive brakes, wood panel products, polyurethane foams, epoxy resins for printed circuit boards etc.Various methods, for example, chemical, biological, photochemical, and electrochemical methods, have been explored for the oxidation of lignin to obtain value-added products.The biotransformation of extracted lignin was observed using microorganism. The spectrophotometric analysis between control and experimental samples showed new peaks in region 230 nm and 280 nm in experimental extract. Further analysis of degraded lignin from selected fungus was done by LC-MS. LC– MS (liquid chromatography-mass spectroscopy) was performed with lignin samples obtained from untreated lignin sample as control and treated lignin sample with microorganism. While the lignin sample which was treated with microorganismsshows several new peaks which indicate the degradation of lignin.In long termagrowaste based processes will lead to development of novel cost-effective process and bio-products of industrial importance involving the rural people, academia and industries on a cost-sharing basis thus leading to a sustainable development.